Current state of resources for japanese flying squid Todarodes pacificus in the northwestern Tatar Strait (Japan Sea) - P. A. Dulenina; E. I. Ustinova; A. A. Dulenin (Известия ТИНРО)
Data on commercial catches of japanese flying squid Todarodes pacificus in the northwestern Tatar Strait in 2003–2019 are analyzed. To assess the resours status in the study area, the relative number (individuals per jigger winch per hour) and biomass (kilograms per vessel per day) marks recognized to be the most applicable winch per hour or the catch in kg per vessel per day. The average CPUE value was 35.6 ± 3.6 ind./winch/hour; increasing trend of CPUE is observed (α = 1.5 ± 0.6, r2 = 0.3, p < 0.03). The squid abundance decreased slightly in the last 2 years, with CPUE decreasing to 28 ind./winch/hour in 2019, though the squid biomass was relatively stable (average CPUE 582.0 ± 45.8 kg/vessel/day) — decreased number of caught individuals was compensated by individual body weight increasing. Long-term tendency to the body weight increasing was noted: the average body weight was 205.0 ± 4.0 g in 2004, 256.0 ± 3.5 g in 2012, and 297.0 ± 6.3 g in 2019. Possible climate change influence on the squid population was discussed. Because of warming in the reproductive area of T. pacificus in the southern Japan Sea, SST in the spawning period reached 20–25 оC and exceeded the value optimal for reproduction and larvae development (15–23 оC), so the squid abundance decreased. On the contrary, in the northern Japan Sea (in the Tatar Strait) the warming caused better conditions for the squid feeding: the higher zooplankton biomass in this area was observed under SST 13–18 оC that is reached every year recently. On the other hand, the Tsushima Current intensifying promoted active migrations of T. pacificus to the northwestern Tatar Strait. These factors of climate warming ensure favorable environments for northward migrations of T. pacificus and forming of dense feeding aggregations in the northwestern Tatar Strait that allows to expect good conditions for the squid fishery in this area in the nearest future.